Evaluation of within-breed genetic diversity in Krishna Valley cattle: an endangered breed of south India - KARTHICKEYAN, S M K; HEPSIBHA, P (The Indian Journal of Animal Sciences, 2014)
Krishna Valley breed, an endangered draught breed of cattle, evaluated for within breed genetic diversity. The study revealed 169 alleles with the observed number of alleles ranging from 3 to 11. The mean PIC value was high (0.6640±0.03) and 21 loci possessed the PIC values of more than 0.5. Despite small size of the population, Krishna Valley breed of cattle possesses moderately high within- breed genetic diversity (0.7075±0.03) resulting from retention of some rare alleles in small frequencies. Overall FIS value indicated that the population has suffered high amount of inbreeding which is due to very small population size and also the practice of non-random mating due to unavailability of bulls. But departure of the majority of the loci from Hardy-Weinberg equilibrium and high FIS value (18.18 %) urge the breeders and policy makers to take immediate conservation measures of the breed.